2022
DOI: 10.3390/foods11040609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Palm Kernel Oil on the Quality, Fatty Acid Profile, and Sensorial Attributes of Young Bull Meat

Abstract: Lipid supplementation through vegetable oils in diets for ruminants can be a nutritional strategy to increase energy density, manipulate ruminal fermentation and change the physicochemical composition and sensorial properties of meat. This study evaluated the optimal dietary inclusion of palm kernel oil (PKO) for Nellore bulls on meat quality. The diets consisted of 0.0, 11.5, 23.0, and 34.6 g/kg dry matter (DM) PKO levels. PKO inclusion did not influence the centesimal composition, pH, color indices, water ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The FA content of PKC was similar to PKO. PKO contained medium-chain FAs (MCFAs) and SFAs, with LA (46.6%) and myristic acid (16.6%) in large amounts (Santos et al, 2022). According to Rahman et al (2022), PKO contained 49.25% LA and 16.30% myristic acid.…”
Section: Content Of Fatty Acidsmentioning
confidence: 99%
“…The FA content of PKC was similar to PKO. PKO contained medium-chain FAs (MCFAs) and SFAs, with LA (46.6%) and myristic acid (16.6%) in large amounts (Santos et al, 2022). According to Rahman et al (2022), PKO contained 49.25% LA and 16.30% myristic acid.…”
Section: Content Of Fatty Acidsmentioning
confidence: 99%
“…Previous studies have shown that myristic acid (hereinafter referred to as MA, IUPAC name: tetradecanoic acid, molecular formula: CH 3 (CH 2 ) 12 COOH, CAS#: 544-63-8), a saturated fatty acid, mainly present in cardamom oil, coconut oil, palm kernel oil, butterfat, and bovine milk, could be used to prepare a variety of foods (11,12). MA could promote the proliferation and differentiation of neural stem cells in vitro (13).…”
Section: Introductionmentioning
confidence: 99%
“…The use of palm kernel cake and oil, byproducts of palm fruit production, can have economic benefits in ruminant feed [ 17 , 18 ], maintaining physicochemical, sensory and meat acceptance characteristics [ 17 , 19 ]. However, it is not known whether palm kernel oil in lamb diets can affect meat quality.…”
Section: Introductionmentioning
confidence: 99%